An improved closed-form solution for laterally-loaded floating monopiles incorporating base moment and shear resistances - Guangwei Cao; Feng Lin; Haoze Chen; Changjie Zheng; Xuanming Ding; Chunyan Wang (Ocean Engineering, 2026)

Exhumation history of the Ningzhen Mountain Belt, South China: Constraints from low-temperature thermochronology - Zhijun He; Guangwei Li; Xinwei Li; Yifan Yang; Cannan Lin (Journal of Asian Earth Sciences, 2026)

Interpretable data-driven modeling of total phosphorus dynamics from 2005 to 2024 in a large shallow lake - Weipeng Lin; Yongqiang Zhou; Ze Ren; Wei Zou; Hongwei Guo; Na Li; Yunlin Zhang; James Elser; R. Iestyn Woolway; Kun Shi; Guangwei Zhu; Boqiang Qin; et al. (Water Research, 2026)

Lack of adverse effects in a subchronic 90-day oral toxicity study of almond hull powder in Sprague-Dawley rats - Yuyang Yao; Juer Liu; Yanling Cheng; Qiming Miao; Xinyue Zhu; Jingyi Xie; Na Zhang; Wei Hua; Guangwei Huang; Xiangyang Lin; Shengquan Mi; Roger Ruan (Food and Chemical Toxicology, 2026)

Study on the pyrolysis interactions of different anatomical parts of flue-cured tobacco stalks and the catalytic cracking characteristics of nicotine - Jinming Zhang; Guangwei Sun; Luqiu Lin; Zhenguo Chen; Hanwen Nie; Xun Gong (Bioresource Technology, 2026)

Seismic response of the composite bucket foundation supported offshore wind turbines under marine environmental loadings - Wei Cheng; Yikang Wang; Ming Li; Guangwei Xu; Haoran Lin; Panpan Shen (Marine Georesources & Geotechnology, 2025)

Study on seeding delay time and lag distance of automatic section control system for maize seeder - Lin Ling; Hanqing Li; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Liwei Li; Rui Liu; Xinguang Huang; Guangwei Wu; Zhijun Meng; Bingxin Yan (Computers and Electronics in Agriculture, 2025)

Research on combustion characteristics of new high energy composite materials − using tungsten powder as fuel and DAP-4 as oxidizer - Guangwei Xiao; Erhai An; Hua Fang; Xueli Zhang; Yingxin Tan; Lin Li; Peng Deng; Zhuoxin Fei; Xiong Cao (Fuel, 2025)

Co-combustion reaction of corn stalk hydrochar and anthracite: Kinetics, mechanism and CO2 emission reduction - Wang Liang; Yihao Cui; Di Zhu; Yihan Chen; Yonghui Han; Lin Yue; Chunhe Jiang; Runsheng Xu; Xiaojun Ning; Jianliang Zhang; Chuan Wang; Guangwei Wang (Fuel, 2025)

Biochar doping of synthesized mordenite improves adsorption and oxidation in As(III) removal: Experiments and DFT calculations - Guangwei Wu; Jing Lin; Bin Wang; Fuyang Huang; Quan Long; Weiguo Tu (Environmental Research, 2025)

Study on performance of a novel asphalt mixture containing strength and morphology controlled artificial aggregates - Guangwei Chen; Xu Yue; Yadong Xie; Lin Kong; Yue Huang; Dongya Ren (Journal of Cleaner Production, 2025)

Regulation of ethanol production from anaerobic fermentation of food waste using aromatic alcohol-based quorum-sensing molecules - Rong Ma; Zhuoshen Huang; Yi Jiang; Anqi Zhao; Guangwei Yu; Changquan Lin; Langping Zhu; Xiaozhi Zhang; Xiaotian Li; Chunming Wang (Journal of Environmental Management, 2025)

The thermal decomposition and combustion properties of DAP-4/FG composite materials - Guangwei Xiao; Erhai An; Xueli Zhang; Yingxin Tan; Tengyue Song; Lin Li; Peng Deng; Xiong Cao (Fuel, 2025)

Response of offshore large-diameter pipe piles in layered poroelastic soil to lateral dynamic loading - Changjie Zheng; Hao Lin; Zhichao Zhang; Xuanming Ding; Guangwei Cao (Ocean Engineering, 2025)

BBB-penetrating magnetoelectric nanoparticles with sustainable Gel formulation for enhanced chemotherapy and reduced postoperative glioma recurrence - Rong Huang; Chenteng Lin; Guangwei Jiang; Meng Zhang; Wenjia Gao; Kamiran Aihemaiti; Qianqian Liu; Jinlong Shi; Wei Shi; Rongqin Huang (Chemical Engineering Journal, 2024)

Correction: Sinomenine protects against atherosclerosis in apolipoprotein E-knockout mice by inhibiting of inflammatory pathway - Zhao Gao; Chao Yang; Guangwei Zeng; Ming Lin; Wei Li; Mengna Sun; Yantao Zhang; Beibei Fan; Yogesh Kumar; Kun Yan (Inflammopharmacology, 2024)

Study on the Active Wave Absorption Methods in Lattice Boltzmann Numerical Wave Tank - Guangwei Liu; Qinghe Zhang; Jinfeng Zhang; Lin Xie (Journal of Marine Science and Engineering, 2024)
The active wave absorption method has been widely employed in numerical wave tanks. The wave absorption performance of active wave absorption methods is investigated within a numerical wave tank based on a lattice Boltzmann method. Specifically, two active wave absorption methods—the classical shallow water method and the extended range method—are compared. By analyzing the contributions of free and bound components in the harmonics of the reflected wave to the reflection coefficient, we found that the extended-range method is more effective than the shallow-water method in absorbing the reflection of the primary harmonic. Moreover, a wave absorption performance index is proposed to carry out rapid evaluation of active wave absorption method performance without resorting to numerical simulations. Our findings indicate that the performance index ratio of two active wave absorption methods closely mirrored their reflection coefficient ratio. Notably, the extended-range method significantly reduces the performance index in both shallow and deep waters, exhibiting superior active absorption performance within the lattice Boltzmann method-based numerical wave tank context compared to the shallow-water method.

Life cycle assessment of carbonaceous pellets used in blast furnaces in the context of “double carbon” - Chunyang Lu; Dengwei Zhang; Jie Ren; Kai Wang; Manqing Li; Chuan Wang; Guangwei Wang; Lin Xiong; Yaowei Yu (Science of The Total Environment, 2024)

PCSK9 regulates myocardial ischemia–reperfusion injury through parkin/pink1-mediated autophagy pathway - Guangwei Huang; Hailong Bao; Peng Zhan; Xiyang Lu; Zonggang Duan; Xinlin Xiong; Muzhi Lin; Bing Wang; Hongxin An; Luanda Xiahou; Haiyan Zhou; Zhenhua Luo; et al. (Molecular & Cellular Toxicology, 2024)

Sinomenine protects against atherosclerosis in apolipoprotein E-knockout mice by inhibiting of inflammatory pathway - Zhao Gao; Chao Yang; Guangwei Zeng; Ming Lin; Wei Li; Mengna Sun; Yantao Zhang; Beibei Fan; Yogesh Kumar; Kun Yan (Inflammopharmacology, 2024)

Influence of speed measurement method on performance of an electric-drive maize precision planter - Lin Ling; Guangwei Wu; Changkai Wen; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Jianhong Ding; Zhijun Meng; Bingxin Yan (Biosystems Engineering, 2024)

Enhancement of immobilized biochar/FeS on nitrogen removal in constructed wetland at low temperature - Guangwei Lin; Yi Ding (Journal of Water Process Engineering, 2024)

Application of sodium alginate/iron sulfide/biochar beads as electron donors to enhance nitrate removal from carbon-limited wastewater - Guangwei Lin; Yi Ding (Chemical Engineering Journal, 2023)

Study on influencing factors of hole-filling performance of rice precision direct seed-metering device with hole ejection - Hanqing Li; Bingxin Yan; Zhijun Meng; Lin Ling; Yanxin Yin; Anqi Zhang; Chunjiang Zhao; Guangwei Wu (Biosystems Engineering, 2023)

Horizontal dynamic response of offshore large-diameter pipe piles - Changjie Zheng; Hao Lin; Guangwei Cao; Lubao Luan (Ocean Engineering, 2023)

Estimating small structural motions from multi-view video measurement - Enjian Cai; Yi Zhang; Xiaodong Ji; Xinzheng Lu; Linlin Xie; Yuncheng Zhuang; Taisen Zhao; Guangwei Lin (Engineering Structures, 2023)

PCSK9 Knockdown Can Improve Myocardial Ischemia/Reperfusion Injury by Inhibiting Autophagy - Guangwei Huang; Xiyang Lu; Zonggang Duan; Kai Zhang; Lei Xu; Hailong Bao; Xinlin Xiong; Muzhi Lin; Chao Li; Yunquan Li; Haiyan Zhou; Zhenhua Luo; et al. (Cardiovascular Toxicology, 2022)

miR-21-5p serves as a promoter in renal cell carcinoma progression through ARHGAP24 downregulation - Bin Meng; Pengfei Wang; Chaofei Zhao; Guangwei Yin; Xin Meng; Lin Li; Shengyong Cai; Chengquan Yan (Environmental Science and Pollution Research, 2022)

The insecticidal crystal protein Cry2Ab10 from Bacillus thuringiensis: cloning, expression, and structure simulation - Yi Lin; Guangwei Fang; Fuying Cai (Biotechnology Letters, 2008)

Characterization of the highly variable cry gene regions of Bacillus thuringiensis strain ly4a3 by PCR-SSCP profiling and sequencing - Yi Lin; Guangwei Fang; Kun Peng (Biotechnology Letters, 2007)